2007
DOI: 10.1521/suli.2007.37.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Risk Factors for Suicidality Between African American and White Patients Vulnerable to Suicide

Abstract: Risk factors for suicidal ideation and attempts have been shown to differ between African Americans and Whites across the lifespan. In the present study, risk factors for suicidality were examined separately by race/ethnicity in a population of 131 older adult patients considered vulnerable to suicide due to substance abuse and/or medical frailty. In adjusted analyses, social support was significantly associated with suicidality in African American patients, while younger age and the presence of an anxiety dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Black participants had lower rates of cutting and higher scores on Rational coping which fits with the idea that self-harm is associated with maladaptive coping styles. Marion and Range (2003) found that among female African American students a collaborative religious problem-solving style acted as a buffer against suicidal behaviour, and research on suicidality among older people in the United States also proposed that Black people may use more active coping styles (Vanderwerker et al, 2007). However, if maladaptive coping styles contribute to self-harm, then participants reporting Emotion focussed and Avoidance coping would be expected to have higher rates of self-harm, which is only partially supported by the current data.…”
Section: Discussionmentioning
confidence: 53%
“…Black participants had lower rates of cutting and higher scores on Rational coping which fits with the idea that self-harm is associated with maladaptive coping styles. Marion and Range (2003) found that among female African American students a collaborative religious problem-solving style acted as a buffer against suicidal behaviour, and research on suicidality among older people in the United States also proposed that Black people may use more active coping styles (Vanderwerker et al, 2007). However, if maladaptive coping styles contribute to self-harm, then participants reporting Emotion focussed and Avoidance coping would be expected to have higher rates of self-harm, which is only partially supported by the current data.…”
Section: Discussionmentioning
confidence: 53%
“…This result was surprising given the considerable literature implicating stronger social support networks in minority populations when examining reasons for the ethnic differences in suicidal ideation and behavior (Bender, 2000;Roy, 2003;Vanderwalker et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…Among African Americans, more social integration and strong reliance upon religious faith as a means of coping with problems were both associated with increasing age. Higher levels of family cohesion and support have been found to be associated with lower levels of suicidal ideation and suicidal risk in African American older adults (Roy, 2003;Vanderwalker et al, 2007). Bender (2000) examined protective factors against suicide in older African American and European American women and found that African American women report stronger reasons for not completing suicide on scale items with regard to family and religion, although total scale scores did not significantly differ.…”
mentioning
confidence: 99%
“…Social support is inversely associated with reported psychological distress (Lincoln et al 2003), suicidal ideation (Lincoln et al 2012b; Vanderwerker et al 2007; Wingate et al 2005), and suicide attempts (Compton et al 2005; Kaslow et al 2005; Lincoln et al 2012b; Vanderwerker et al 2007). Finally, emerging research on negative aspects of social relationships reveals that, among African Americans, individuals experiencing higher levels of negative interaction are more likely to report depressive symptoms and have a higher likelihood of being diagnosed with depression (Lincoln and Chae 2012; Lincoln et al 2005).…”
Section: Social Support and Well-being Among Aging African Americansmentioning
confidence: 99%